Diurnal Characteristics of Summer Precipitation Over Luzon Island, Philippines - Hilario, Miguel Ricardo (Archīum Ateneo, 2020)
A network of 411 ground stations across Luzon Island, Philippines (12.5–20° N, 119–126.5° E) was used to characterize the diurnal cycles of summer precipitation, in terms of amount (PA), frequency (PF), and intensity (PI), during the southwest monsoon season (SWM; May–September) between 2011 and 2018. In addition to monsoon exposure, the effect of topography on the diurnal cycle of precipitation also was investigated by comparing a valley, plain, west- and east-facing coasts near mountains. Results show that monsoon exposure significantly influenced diurnal precipitation such that PA and PF decreased (PI increased) toward the leeward side of Luzon Island. Most topographies showed late afternoon-early evening peaks; however, the east-facing coast exhibited a late night-early morning peak. Orographic effects led to a high PA over mountains and enhanced the spatiotemporal propagation of PA in monsoon-exposed areas. The first (second) half of the diurnal peak exhibited high PI/low PF (low PI/high PF), suggesting both PI and PF are important indicators of PA. Finally, graded analysis revealed that light precipitation (0.01–2.5 mm h−1) captured overall precipitation trends across Luzon Island, highlighting the importance of this intensity of precipitation. Heavy precipitation (2.5–7.5 mm h−1) peaked in the morning; however, underlying mechanisms remain unknown. The study presents the first examination of the diurnal precipitation cycle in Luzon Island using a dense network of synoptic stations. The study demonstrates the complex effect of topography on precipitation and the importance of the SWM in the diurnal cycle of precipitation.